2019
DOI: 10.7150/jca.32092
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression Network Analysis Identified Gene Signatures in Osteosarcoma as a Predictive Tool for Lung Metastasis and Survival

Abstract: Osteosarcoma (OS) is the most common primary bone tumor, whose poor prognosis is mainly due to lung metastasis. The aim of this study is to build a practical and valid diagnostic test that can predict the risk of OS metastasis and progression. We performed weighted gene co-expression network analysis (WGCNA) on GSE21257 from the Gene Expression Omnibus (GEO) database, which contains microarray data of biopsies from OS patients. In these modules, the highest association was found between the blue module and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…WGCNA is a powerful tool for analysing multiple genes in large-scale datasets. It has been extensively used to explore gene co-expression modules and hub genes as potential target biomarkers in many cancers (Foroughi et al, 2018;Chen et al, 2018;Giulietti et al, 2016;Liu et al, 2019;Wang et al, 2019a;Wang et al, 2019b;Xu et al, 2018;Zhai et al, 2019;Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c). In the current study, we applied WGCNA and systematically identified the turquoise module as the most significantly negatively associated (r = −0.2, P = 4e−04) with pathologic stage for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…WGCNA is a powerful tool for analysing multiple genes in large-scale datasets. It has been extensively used to explore gene co-expression modules and hub genes as potential target biomarkers in many cancers (Foroughi et al, 2018;Chen et al, 2018;Giulietti et al, 2016;Liu et al, 2019;Wang et al, 2019a;Wang et al, 2019b;Xu et al, 2018;Zhai et al, 2019;Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c). In the current study, we applied WGCNA and systematically identified the turquoise module as the most significantly negatively associated (r = −0.2, P = 4e−04) with pathologic stage for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Another study (Ding et al, 2019) have also reported that the pseudopodium-enriched atypical kinase 1-PPP1R12B axis inhibits colorectal tumourigenesis and metastasis through the deactivation of the Grb2/PI3K/Akt pathway, which might provide a novel therapeutic strategy for CRC treatment. The hub gene CFD was identified and validated as a potential target gene in papillary thyroid cancer (Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c). CRYAB is a very important protein involved in a variety of signal transduction pathways, including apoptosis, inflammation and oxidative stress (Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations